2022
DOI: 10.3390/su142114515
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Radon in Groundwater and the Corresponding Human-Health Risk Assessment in Northeastern Saudi Arabia

Abstract: Radon is one of the most common human exposures as a natural radiation source and can cause lung, colon, and stomach cancer. In this study, groundwater from different wells was collected from the northeastern part of Saudi Arabia. The radon concentration was estimated using an electronic portable radon detector RAD7 with a big-bottle system. The annual effective dose of radon exposure by the ingestion and inhalation of water is calculated using the radon concentration for different age groups to assess the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…As expected, the calculated annual effective doses for infants were relatively higher than those for children and adults. This is consistent with the observations of (Mamun & Alazmi, 2022). The obtained results showed a significant difference between the doses estimated for infants and children age groups.…”
Section: Annual Effective Dosesupporting
confidence: 92%
See 3 more Smart Citations
“…As expected, the calculated annual effective doses for infants were relatively higher than those for children and adults. This is consistent with the observations of (Mamun & Alazmi, 2022). The obtained results showed a significant difference between the doses estimated for infants and children age groups.…”
Section: Annual Effective Dosesupporting
confidence: 92%
“…The values obtained for the present study's annual effective dose due to inhalation were approximately the same as those of the annual effective dose due to adult ingestion. This finding is consistent with the observations of Mamun & Alazmi, 2022.. The obtained values were below the recommended limit of 100 μSva -1 of the WHO (WHO, 2017).…”
Section: Annual Effective Dosesupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, Al Mamun et al investigated radon in groundwater and the associated health risk in northern Saudi Arabia. They concluded that the assessed risk due to radon exposure was in the safe limit set internationally (Mamun et al, 2022). Al-Ghamdi performed radioactivity measurements in twenty groundwater in Al-Baha region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%